Detection of falsification of horilka by admittance spectroscopy - Pokhodylo Yevhen; Kuts Viktor; Stasyshyn Yuriy (Lviv Politechnic Publishing House, 2021)
The methods of quality control of horilka by electrical parameters, in particular, dielectric constant, specific conductivity, and imitation components are analyzed. The research results of individual samples of alcohol solutions and horilkas of different brands by the method of admittance spectroscopy were also analyzed. Based on this, methods for detecting falsification of horilka products by the method of admittance spectroscopy are proposed. The reactive component of the control object's ad is selected as an informative parameter. Two types of falsification are analyzed. The first is the falsification of the original horilka by replacing it with an aqueous-alcohol solution. The second – by replacing one brand of horilka with another. The analysis of the obtained results of researches of two types of objects on reactive components of their admittance in the frequency range 100 Hz – 100 kHz showed the following: characteristic features of dependencies of reactive components on frequency are revealed; they have been found to have extreme values at different frequencies. The reactive component of the admittance of aqueous-alcohol solutions reaches an extreme value at the beginning of the range. The same component of the original horilkas of different brands has extreme values at the end of the range. Based on this, methods for prompt detection of falsifications are proposed.
Keywords: Reactive component; Admittance; Alcohol; Quality; Falsification